Pelatihan dan Pendampingan Pencatatan Keuangan Masjid Berbasis Aplikasi - Media Kusumawardani; Achmad Soediro; Muhammad Farhan; Fardinant Adhitama (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2022)
The mosque's financial responsibilities can be presented in the financial statements. Generally, the mosque's financial report is a simple financial report that only records income and expenses. The mosque's financial statements have not been based on PSAK 45 and PSAK 109. This problem was also carried out by the Al Hidayah Mosque, Bukit Besar Palembang, South Sumatra. Al Hidayah Mosque still records manually and only records cash flows. Community service activities are carried out to help Al Hidayah Mosque in solving problems. The solution offered is the provision of materials to improve management's understanding in recording financial reports, providing applications that can be used easily. While the implementation method used is interactive discussion in the delivery of material and tutorials on using the application. Based on feedback from participants, the implementation of community service has a positive impact on the management of the Al Hidayah Mosque, especially in increasing the understanding of mosque finances and reducing financial recording problems at the Al Hidayah Mosque. Suggestions that can be given to the management of the Al Hidayah Mosque are to maintain consistency in mosque financial records based on PSAK 45 and PSAK 109